2022
DOI: 10.1111/ijfs.15619
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gluten‐Free Muffins made from Breadfruit and Unripe Plantain Flours

Abstract: Inclusion of breadfruit (BF) and unripe plantain (UP) in gluten‐free muffins was investigated along with a 1:1 BF/UP blend muffin and compared to controls made with gluten‐free rice (RI) or traditional wheat (WH) flour. The alternative flours had a 10% higher fibre content than WH and 2%–4% higher than RI flours. Muffin batter viscosity of RI and WH was initially much lower (3‐10 times) than UP, BF and BF/UP blend batter. Additionally, starch gelatinisation temperature was increased by 4%–14% for batter made f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…It was reported that mature green plantain pulp is rich in sugar (2 %-31 %), micronutrients, such as potassium (440 mg/100 g), phosphorus (32 mg/100 g), and also magnesium (32 mg/100 g), vitamin C (20 mg/100 g), and vitamin B (Daniells, Englberger, & Lorens, 2011;Sauco, 2010). Unripe plantain flour has been shown to contain resistant starch which makes the flour to be classified as rich fiber food (Olawuni, Uruakpa, & Uzoma, 2018) Muffin produced from composite flour of unripe plantain and breadfruit had s 10 % fiber content higher than the whole wheat muffin and increased in starch gelatinization temperature which could have structural benefits to baked muffins (Kemski, Cottonaro, Vittadini, & Vodovotz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that mature green plantain pulp is rich in sugar (2 %-31 %), micronutrients, such as potassium (440 mg/100 g), phosphorus (32 mg/100 g), and also magnesium (32 mg/100 g), vitamin C (20 mg/100 g), and vitamin B (Daniells, Englberger, & Lorens, 2011;Sauco, 2010). Unripe plantain flour has been shown to contain resistant starch which makes the flour to be classified as rich fiber food (Olawuni, Uruakpa, & Uzoma, 2018) Muffin produced from composite flour of unripe plantain and breadfruit had s 10 % fiber content higher than the whole wheat muffin and increased in starch gelatinization temperature which could have structural benefits to baked muffins (Kemski, Cottonaro, Vittadini, & Vodovotz, 2022).…”
Section: Introductionmentioning
confidence: 99%